2016
DOI: 10.1088/1752-7155/10/1/016014
|View full text |Cite
|
Sign up to set email alerts
|

Association between exhaled inflammatory markers and asthma control in children

Abstract: The relationship between exhaled inflammatory markers and asthma control in children is unclear. To explore the association between inflammatory markers in exhaled breath (fractional nitric oxide (FeNO), volatile organic compounds (VOCs), cytokines/chemokines) and asthma control. To assess whether exhaled inflammatory markers are able to discriminate between children with persistently controlled/uncontrolled asthma. 96 asthmatic children were followed-up in a one-year observational study. Every 2 months, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 36 publications
(58 reference statements)
3
37
0
1
Order By: Relevance
“…The novelty of the present study is represented by the prospective follow‐up of breathomics in asthma patients during the loss and recovery of clinical control. Our data therefore extend previously published cross‐sectional data in adults and longitudinal data in children, demonstrating various accuracies in discriminating controlled and uncontrolled asthma by GC/MS analysis of exhaled breath. In addition, the present study independently confirms and extends previous data on eNose signals during loss of control by withdrawal and restoration of steroids in asthma by van der Schee et al Our data are demonstrating the longitudinal changes in eNose signal between baseline, loss of control and recovery, whilst relating those to the course of symptoms, lung function and inflammatory cell counts in sputum.…”
Section: Discussionsupporting
confidence: 87%
“…The novelty of the present study is represented by the prospective follow‐up of breathomics in asthma patients during the loss and recovery of clinical control. Our data therefore extend previously published cross‐sectional data in adults and longitudinal data in children, demonstrating various accuracies in discriminating controlled and uncontrolled asthma by GC/MS analysis of exhaled breath. In addition, the present study independently confirms and extends previous data on eNose signals during loss of control by withdrawal and restoration of steroids in asthma by van der Schee et al Our data are demonstrating the longitudinal changes in eNose signal between baseline, loss of control and recovery, whilst relating those to the course of symptoms, lung function and inflammatory cell counts in sputum.…”
Section: Discussionsupporting
confidence: 87%
“…The authors found no statistically significant association between asthma control levels and inflammatory markers. However, a model comprising of 15 VOCs could successfully discriminate between children with persistently controlled and uncontrolled asthma with good prediction accuracy (AUROC‐curve 86%) …”
Section: Current Statusmentioning
confidence: 99%
“…The authors found no statistically significant association between asthma control levels and inflammatory markers. However, a model comprising of 15 VOCs could successfully discriminate between children with persistently controlled and uncontrolled asthma with good prediction accuracy (AUROC-curve 86%) 37. As mentioned earlier, one of the clinical objectives of VOCs in exhaled breath is the prediction of exacerbations in asthmatic children.Promising results on this topic have been reported byRobroeks et al 38 in 2013, and recently by van Vliet et al39 In a 1-year prospective study, F E NO, VOC profiles, lung function, and clinical symptoms were determined for a small group of 40 children with asthma, every 2 months.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, they concluded that induced sputum is not reliable for assessing lower airway eosinophilic inflammation in preschool children. In a longitudinal observation study of 96 children aged 6‐18 years, asthma control assessed by the asthma control test (ACT) was compared with exhaled breath nitric oxide (NO) and volatile organic compounds (VOC); there was no association between these exhaled markers and ACT, though a subset of exhaled VOC were identified that could categorize children with controlled versus uncontrolled asthma . Thomas et al showed that agreement between metacholine challenge test results, exhaled nitric oxide, and quality of life was poor in children with asthma, emphasizing that these parameters show different aspects of the disease and only a composite evaluation using all these tools can give us the big picture.…”
Section: Asthmamentioning
confidence: 99%